The Aftermath of Deportation: Effects on the Family - Gonzalez, Nelly; Morgan, Melissa (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2013)
The primary aim of this qualitative study was to understand how Latino/a families in the United States are affected when a family member is deported. The U.S. Census Bureau (2008) reports that 4% of the population is undocumented immigrants and that 47% of households with an undocumented immigrant are family households (e.g. have a spouse or child). Given this large number of families liable for experiencing deportation, the need to conduct a study exploring this phenomenon seemed important. Five individuals who identified as Latino/a and who had a family member deported were interviewed and data was analyzed following a phenomenological approach. Five main themes emerged: lifestyle changes and adjustments, social support, impact on family unit, impact on individual family members, and solutions to family separation. These results are discussed as well as possible implications.